2011
DOI: 10.1111/j.1365-2915.2011.00991.x
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of climate, host and landscape factors on Culicoides species in Scotland

Abstract: Culicoides biting midges (Diptera: Ceratopogonidae) vector a wide variety of internationally important arboviral pathogens of livestock and represent a widespread biting nuisance. This study investigated the influence of landscape, host and remotely-sensed climate factors on local abundance of livestock-associated species in Scotland, within a hierarchical generalized linear model framework. The Culicoides obsoletus group and the Culicoides pulicaris group accounted for 56% and 41%, respectively, of adult fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 42 publications
5
80
1
2
Order By: Relevance
“…For more temperate species, Baldet et al (2008) did not observe any activity outdoors when the maximum temperature fell below 10.8 C and the minimum temperature below 5.8 C. Purse et al (2011) and Scolamacchia et al (2014) found that the best performing models based on a single set of predictors were climate models, followed by landscape and then host models. The main climatic factors that influence distribution, abundance and seasonality of Culicoides spp.…”
Section: Additional Informationmentioning
confidence: 99%
“…For more temperate species, Baldet et al (2008) did not observe any activity outdoors when the maximum temperature fell below 10.8 C and the minimum temperature below 5.8 C. Purse et al (2011) and Scolamacchia et al (2014) found that the best performing models based on a single set of predictors were climate models, followed by landscape and then host models. The main climatic factors that influence distribution, abundance and seasonality of Culicoides spp.…”
Section: Additional Informationmentioning
confidence: 99%
“…1 km, Kluiters et al, 2013) or at different scales (e.g. between 1 and 8 km, Calvete et al, 2008;Purse et al, 2011). However, as previously shown (Hamer and Hill, 2000), the selection of the spatial scales affects the outcome of the modelling, e.g.…”
Section: Introductionmentioning
confidence: 91%
“…Since the availability of digital datasets of land cover, temperature, or potential hosts is continuously increasing, several studies have also used this kind of data to predict the prevalence of biting midge species, e.g. the normalised difference vegetation index (NDVI) (Purse et al, 2004;Calvete et al, 2008;Kluiters et al, 2013) or the CORINE land cover data (Kirkeby et al, 2009;Purse et al, 2011). These data are available or used on different scales raising the question, which spatial scale, or scales, should be chosen to reach the best possible predictions for different biting midge species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zimmer et al (2009) avaient également observé cette même espèce au sein d'une prairie bovine mais pas dans l'étable correspondante. L'espèce C. punctatus, récemment identifiée comme un vecteur possible du SBV (Larska et al 2013) et dont l'abondance semble notamment corrélée à la présence de moutons (Purse et al 2012), est relativement bien représentée en prairie ovine (8,8% du total des captures) mais aucun spécimen n'a été observé dans la bergerie ; cela pourrait s'expliquer par la localisation des gîtes larvaires. Le nombre de spécimens de l'espèce C. chiopterus est quant à lui probablement sous-estimé, comme démontré par Carpenter et al (2008b) pour les piégeages lumineux, puis confirmé par Griffioen et al (2011).…”
Section: Traitement Des éChantillons Et Analyseunclassified